ALMA observations of gas and dust towards embedded protostellar envelopes in Serpens South - Garces, Juan (2021)
Protostellar sources are characterized by continuum emission, as well as molecular emission tracing the gaseous envelope. The morphology and kinematics of the envelope are useful to study physical characteristics of protostellar candidates and their evolution, revealing aspects of the still unknown process of star formation. Our aim is to study protostars within the very young, active, and relatively nearby Serpens South cluster by analyzing their dense C18O envelopes/disks, enhancing the continuum source census of Plunkett et al. (2018). Most of these sources lie within a predominant filamentary structure. 67 protostellar candidates have been identified as continuum and/or IR sources, and the C18O data have been imaged by combining ALMA 12m-array, 7m-array, and single dish observations. The C18O spectra were organized in different groups according to their spectral shape and intensity. Also, given the fact that this region is embedded in a filamentary structure, we have made attempts to identify the level of line emission contribution that is most probably due to the filament instead of the source candidate itself. Finally, ongoing work will investigate possible trends associated to mass distribution among the filament, relations between source class, mass and C18O intensity, and different kinematic models to fit the envelopes´ motions.